2013
DOI: 10.1590/0037-8682-1665-2013
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of canine leptospirosis in the metropolitan area of Curitiba, State of Parana, Southern Brazil

Abstract: Revista da Sociedade Brasileira de Medicina Tropical 46(6):772-775, Nov-Dec, 2013http://dx.doi. org/10.1590/0037-8682-1665-2013 Short Communication ABSTRACT Introduction:The incidence of canine leptospirosis in Brazil needs to be assessed. Methods: The same dogs in southern Brazil were sampled over two years to determine the prevalence, incidence and association of canine leptospirosis with various risk factors. Results: In 2009, the prevalence was 33 (14.4%) of 228 dogs, with a predominance of serovar Can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 5 publications
(5 reference statements)
3
9
0
Order By: Relevance
“…Several recent studies have examined the de- mographic profile of seropositive dogs for Leptospira spp., but results are ambiguous 29 . Dogs with street access were more likely to be exposed to the agent than those domiciled, similar to studies by Martins et al 20 , whereas in other studies there was no difference in the management 30,31 . Similar to stray dogs, dogs with street access are exposed to several environments, with the habit of drinking sewage and ponds water, bathe in these waters in order to mitigate the heat and rummage the garbage, as was observed during the research.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Several recent studies have examined the de- mographic profile of seropositive dogs for Leptospira spp., but results are ambiguous 29 . Dogs with street access were more likely to be exposed to the agent than those domiciled, similar to studies by Martins et al 20 , whereas in other studies there was no difference in the management 30,31 . Similar to stray dogs, dogs with street access are exposed to several environments, with the habit of drinking sewage and ponds water, bathe in these waters in order to mitigate the heat and rummage the garbage, as was observed during the research.…”
Section: Discussionsupporting
confidence: 81%
“…The seroprevalence of 13.8% obtained in this study was considered low, since canine leptospirosis is endemic in practically all Brazilian regions, with an average of 26% of dogs reacting to the MSA 18 test. In Brazil, seroprevalence values for canine leptospirosis vary from 6.6% to 85% and, in particular, in the Northeast, 7% and 85% rates have been reported 19,20 . Factors related to the epidemiology of infection, such as animal density, rainfall, cropping system, soil type, occurrence of other animal species and access to water explain the gaps between prevalence rates 21 .…”
Section: Discussionmentioning
confidence: 99%
“…The Brazilian Ministry of Health has established a unified mandatory notification system for suspected human leptospirosis cases, which provides epidemiological information on endemicity nationwide. Despite subpar notification rates due to lack of diagnosis and mild or non-attended cases, Parana was ranked fifth out of 26 Brazilian states and the national capital in 2015, with 362/3,257 (11.11%) of the total human confirmed cases, of which 18/362 (4.97%) cases and 07/18 (38.88%) deaths were reported in Londrina; a similar pattern with 05/14 (35.71%) deaths was observed in 2016 (42). The human seroprevalence results of 11/597 (1.84%) in the current study may corroborate the only two human studies from the same region, which have found 25/207 (12.1%) human cases near (33 km) Londrina city (33) and 2/157 (1.27%) cases among veterinary students in the northwestern Parana State (43).…”
Section: Discussionmentioning
confidence: 61%
“…Those studies demonstrated that Leptospira infection is not a rare event in dogs and that the point prevalence is context dependent. One study reported an incidence of 28.9% per year (25) in a community with socioeconomic and environmental characteristics similar to those of Vila Pantanal, but because the follow-up interval period was one year, infections may have gone undetected. Interestingly, in our study, we were able to ascertain that 20 out of 79 (25%) dogs infected during the overall period were infected more than once throughout the year.…”
Section: Discussionmentioning
confidence: 99%
“…(17) , 30.5% in dogs treated in a Veterinary Teaching Hospital in Northern State (24) , and 32.2% (n = 598) in diagnostic serum samples taken from dogs in Curitiba (23) . Only one study of incidence rates in dogs has been conducted, which reported an annual incidence of 28.9% in a slum community of Curitiba City (25) . As such, the present study aimed to evaluate the seroprevalence and seroincidence of canine leptospirosis in an endemic slum community via four follow-up samplings throughout a single year.…”
mentioning
confidence: 99%